HOLISTICS JOURNAL - Holistics Journal (HOLISTICS, 2020)
Prof. Sofendi, Ph,D., Universitas Negeri Sriwijaya, Palembang Dr. Rita Inderawati, M.Pd., Universitas Negeri Sriwijaya, PalembangProf. Dr. Indawan Syahri, M.Pd., Universitas Muhammadiyah, Palembang Dr. Sunda Ariana,  M.Pd., M.M.,  Universitas Bina Darma, PalembangDr. Dian Ekawati, M.Pd., Lembaga Penjamin Mutu Pendidikan, Palembang Dr. A. Gumawang Jati, M.A., Institut Teknologi Bandung, BandungDr. Yuli Utanto, M.Si., Universitas Negeri Semarang, Semarang Dr. Een Y. Haenilah, Universitas Negeri Lampung, LampungDr. Nurlaelah, M.Hum., Universitas Muslim Indonesia, Makassar Drs. Deddy Suryana, M.A., Universitas Pendidikan Indonesia, BandungDr. Alimin Laundung, M.Pd., Politeknik Negeri Makassar, Makassar Drs. Zubaidi, Dipl. TESL, M.Pd., Politeknik Negeri Malang, MalangI Nyoman Rajin Aryana, S.Pd., M.Hum., Politeknik Negeri Bali, Bali Dr. Mulyadi, M.A., Universitas PGRI, PalembangDrs. Iman Suroso, M.Pd., Politeknik Negeri Semarang, Semarang